2015
DOI: 10.1111/cas.12842
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐suppressive microRNA‐223 inhibits cancer cell migration and invasion by targeting ITGA3/ITGB1 signaling in prostate cancer

Abstract: Analysis of microRNA (miRNA) expression signatures in prostate cancer (PCa) and castration‐resistant PCa has revealed that miRNA‐223 is significantly downregulated in cancer tissues, suggesting that miR‐223 acts as a tumor‐suppressive miRNA by targeting oncogenes. The aim of this study was to investigate the functional roles of miR‐223 and identify downstream oncogenic targets regulated by miR‐223 in PCa cells. Functional studies of miR‐223 were carried out to investigate cell proliferation, migration, and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 42 publications
5
108
0
Order By: Relevance
“…Usually, miR-223 was considered to be a suppressor in multiple cancers, such as cervical cancer [28], bladder cancer [29], prostate cancer [30] and breast cancer [31]. Our results were consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Usually, miR-223 was considered to be a suppressor in multiple cancers, such as cervical cancer [28], bladder cancer [29], prostate cancer [30] and breast cancer [31]. Our results were consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicate that miR-223-3p plays vital roles in a variety of tumor types, either as an oncogene or tumor suppressor depending on the cellular contexts. Consistent with its dual role, miR-223-3p has been shown to function as an oncogene in T-cell acute lymphoblastic leukemia, gastric and lung cancers (13,15,21,27,28), and as a tumor suppressor in cutaneous T-cell lymphoma and prostate cancer (29,30). Given its diverse function in different cancer types, we characterized the functional role of miR-223-3p in TGCT cells.…”
Section: Discussionmentioning
confidence: 87%
“…MiR-223 has been implicated in numerous physiological and pathological processes [29-31], and several studies have reported that miR-223 is associated with myocardial diseases. Lu et al reported that miR-223 was upregulated in left ventricular biopsies from patients with type 2 diabetes and that overexpressing miR-223 increased glucose uptake by upregulating Glut4 protein expression [32].…”
Section: Discussionmentioning
confidence: 99%